The effect of ANKK1 Taq1A and DRD2 C957T polymorphisms on executive function: A systematic review and meta-analysis. (May 2019) - Klaus, Kristel; Butler, Kevin; Curtis, Ffion; Bridle, Chris; Pennington, Kyla
Highlights: The associations of ANKK1 Taq1A and DRD2 C957T with executive function (EF) were explored. The genetic associations with EF were systematically investigated in healthy adults. Separate meta-analyses were carried out for each polymorphism and EF domain. The results suggested a limited effect of these polymorphisms on EF. Results suggested high variability in the EF tests and study populations. Abstract: Research in healthy adults suggests that C957T polymorphism of the dopamine D2 receptor encoding DRD2 and the Taq1A polymorphism of the neighbouring gene ankyrin repeat and kinase domain containing 1 ( ANKK1 ) alter dopaminergic signalling and may influence prefrontally-mediated executive functions. A systematic review and meta-analysis was carried out on the evidence for the association of DRD2 C957T and ANKK1 Taq1A polymorphisms in performance on tasks relating to the three core domains of executive function: working memory, response inhibition and cognitive flexibility in healthy adults. CINAHL, MEDLINE, PsycARTICLES and PsychINFO databases were searched for predefined key search terms associated with the two polymorphisms and executive function. Studies were included if they investigated a healthy adult population with the mean age of 18–65 years, no psychiatric or neurological disorder and only the healthy adult arm were included in studies with any case-control design. Data from 17 independent studies were included in meta-analysis, separated by the Taq1A and C957T polymorphisms and by executive function tests: working memory (Taq1A, 6 samples, n  = 1270; C957 T, 6 samples, n  = 977), cognitive flexibility (C957 T, 3 samples, n  = 620), and response inhibition (C957 T, 3 samples, n  = 598). The meta-analyses did not establish significant associations between these gene polymorphisms of interest and any of the executive function domains. Theoretical implications and methodological considerations of these findings are discussed.